Expansion as a Culture-Creating Principle of Post-Modernity: Semantic Contexts and Aesthetic Practices - Marchenko, Oleksii; Pushonkova, Oksana; Gladun, Olha; Kolomiiets, Olena; Protsyshyn, Volodymyr; Pianzin, Serhii (Journal of Education Culture and Society, 2023)
Aim. The purpose of the study is to analyse the structural aspects of expansion, which find expression in cultural metaphors and philosophical concepts, the transformation of the content of which is evidence of the emergence of new aesthetic practices.Methods. The research methodology involves the use of a systemic approach and such methods as analytical, comparative, axiological, and hermeneutic to understand the patterns of formation of paradigms of visual culture and contexts of expansion in postmodern culture.Results. The metaphor of glass during the 20th century loses its meaning as a source of the effects of refraction of reality in perception, the excessive complexity of which forms a tendency for simplifying and zeroing. The expansion becomes an important principle of cultural dynamics, extends to space and time, communication and identity in the world of the rapid circulation of information and its instant obsolescence. The patterns of expansion are observed in the processes of aestheticisation and aesthetic experience as the breaking out of form, perspective, perception and inclusion of the Self in the profound contexts of collective practices.Conclusions. Through mastering new sensual modalities in the photo, film reality, and the latest Internet technologies, there is an expansion of perception as an expansion of media. Therefore, at the level of identity the practices of focus, concentration, and slow contemplation gain importance. In the cultural aspect, the expansion enables a return to tradition in a new capacity.